DAMPAK GEREJA RUMAH DAN PERTUMBUHAN IMAN TERHADAP MISI PENGINJILAN YANG DIMODERASI OLEH KEPEMIMPINAN - Ivo Christiana Siregar; Heryanto (Sekolah Tinggi Teologi Arastamar Bengkulu, 2023)
This study aims to reveal the impact of house churches and faith growth moderated by leadership in realizing evangelistic missions during the Covid-19 pandemic. This quantitative study uses the Structural Equation Model (SEM) method with Smart PLS software. The population comprises 72 respondents consisting of pastors, teachers, lecturers, evangelists, and business people from various denominations in various regions who worship at home by watching live streaming or building worship involving family members. The results of the research show: house church, faith growth and leadership together affect the evangelism mission by 52.6%, which means there are still 47.4% of other variables that can affect the evangelism mission. Leadership proved unable to strengthen the influence of house churches and faith growth in evangelistic missions during the Covid-19 epidemic. So church leaders need to build a house church practice concept that encourages faith growth that impacts evangelistic missions during the Covid-19 pandemic.